Musculoskeletal biomechanics in sit-to-stand and stand-to-sit activities with stroke subjects: a systematic review - Christina Danielli Coelho de Morais Faria; Viviane Amaral Saliba; Luci Fuscaldi Teixeira-Salmela
INTRODUCTION: Sit-to-stand and stand-to-sit are two of the most mechanically demanding activities undertaken in daily life and which are usually impaired in stroke subjects. OBJECTIVES: To determine the distinguishing characteristics in musculoskeletal biomechanical outcomes of the sit-to-stand and stand-to-sit activities with stroke subjects, with an emphasis on the clinical management of stroke disabilities, in a systematic review. MATERIAL AND METHODS: An extensive literature search was performed with the MEDLINE, CINAHL, EMBASE, PEDro, LILACS, and SciELO databases, followed by a manual search, to select studies on musculoskeletal biomechanical outcomes in both activities with stroke subjects, without language restrictions, and published until December/2007. RESULTS: Out of the 432 studies, only 11 reported biomechanical outcomes of both activities and none reached the total score on the selected quality parameters. The majority of the experimental studies which compared groups did not achieve acceptable scores on their methodological quality (PEDRo). The investigated conditions and interventions were also restricted. Only one study compared biomechanical outcomes between the activities, but only evaluated the time spent to perform them. Few musculoskeletal biomechanical outcomes have been investigated, being weight bearing on the lower limbs and duration of the activities the most investigated. CONCLUSION: There is little information regarding musculoskeletal biomechanical outcomes during these activities with stroke subjects and no definite conclusions can be drawn regarding the particularities of these outcomes on their performance with stroke survivors.